Tantangan dalam Meningkatkan Kepatuhan Wajib Pajak UMKM di Kota Kupang - Made Denny Oktariyana; Thobias E. D. Tomasowa; Olivia Latumahina; Ni Putu Dessy Eka Aryani (Jurnal Inovasi Akuntansi (JIA), 2025)
This study aims to analyze the effect of the level of tax understanding, digitalization of tax services, and tax sanctions on taxpayer compliance of Micro, Small, and Medium Enterprises (MSMEs) in Kupang City. This quantitative study uses a survey method with a questionnaire distributed to 100 MSME taxpayers registered at the Kupang Pratama Tax Service Office (KPP), have a turnover of not more than 4.8 billion, and use digitalization of tax services. The sampling technique used is accidental sampling. Data were analyzed using multiple linear regression. The results of the study indicate that partially, the level of tax understanding, digitalization of tax services, and tax sanctions have a significant positive effect on MSME taxpayer compliance. In addition, simultaneously, the three independent variables also have a significant effect on MSME taxpayer compliance. This study implies the importance of increasing tax understanding, optimizing digitalization of tax services, and effective enforcement of tax sanctions in increasing MSME taxpayer compliance in Kupang City.